A comparison of pain scales in Thai children. Issue 3 (21st February 2005) - Newman, C J; Lolekha, R; Limkittikul, K; Luangxay, K; Chotpitayasunondh, T; Chanthavanich, P
Abstract : Three commonly used pain scales, the visual analogue scale, the Wong-Baker Faces Pain Scale, and the Faces Pain Scale Revised were administered to 122 Thai children, of whom half were HIV infected, in order to assess their validity. These scales presented moderate to good correlation and moderate agreement, sufficient for valid use in Thai children.